THE EFFECT OF KNOWLEDGE MANAGEMENT AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT PERKEBUNAN NUSANTARA IV UNIT KEBUN TINJOWAN - Annisa, Dian; Dirbawanto, Nana Dyki (Transpublika Publisher, 2022)
This study aims to determine and analyze the effect of Knowledge Management and Work Environment on Employee Performance at PT. Perkebunan Nusantara IV Afdeling VI Tinjowan Plantation Unit. This research employs a quantitative associative methodology. This study's sample consisted of PT personnel alone. At the Perkebunan Nusantara IV in Afdeling VI of the Tinjowan Plantation unit, there were 75 respondents. Validity and reliability tests, classical assumption tests, multiple linear regression analysis tests, hypothesis tests using t-tests and f-tests, and coefficient of determination tests are used for data analysis. Based on the findings of the study, it was determined that the knowledge management variable had a partial effect on employee performance, as indicated by the fact that Tstatistic (4,078) > Ttable (1,993), and that knowledge sharing was the indicator that became problematic for this variable. While the work environment variable has a partial effect on employee performance, as demonstrated by the value Tstatistic (7,844) > Ttable (1,993), the transportation indicator becomes an issue in this variable. Fstatistic 31,106 > Ftable (3,12), R = 0,681, and the Adjusted R Square value for this study is 0,449. Hence, the remaining 55,1% of the variance is not explained by employee performance and knowledge management and work environment influenced by issues outside the scope of this study.